Uji Kualitas Tanah Berdasarkan Indeks Kualitas Tanah pada Lahan Sawah di Kawasan Pesisir DAS Unda Kecamatan Klungkung dan Dawan - Sania Permata Ramadani; I Dewa Made Arthagama; I Made Adnyana (Nandur, 2023)
Increasing the use of agricultural land will have an impact on decreasing soil quality, so it is necessary to carry out appropriate soil management to maintain sustainability and optimize productivity on agricultural land which is getting narrower and narrower. Inappropriate soil management systems cause a decrease in land productivity so that crop production is not optimal. This research was conducted in the rice fields of Klungkung and Dawan District from October 2022 until January 2023. This research was conducted using survey methods, soil analysis in the laboratory, and determination of soil quality. Soil samples were taken by purposive sampling technique on each homogeneous land unit. Soil quality indicators measured as minimum data sets (MDS): bulk density, texture, porosity, field capacity water content, pH, C-Organic, CEC, base saturation, nutrients (N, P and K), and C -biomassa. The results of soil quality determination at each homogenous land units are mapped with QGIS 3.16 software and then the land management direction is determined for each homogenous land units. The results showed that the soil quality at the research location was classified as good at homogenous land units I and III and very good at homogenous land units II. The limiting factors in the study area include: texture, N, field capacity water content and C-biomass. It is recommended to cultivate the soil using a tractor and fertilize it with manure, urea in rice fields of the Coastal Area of the Unda Watershed, Klungkung and Dawan District.